Analisis Laporan Arus Kas untuk Menilai Kinerja Keuangan Perusahaan di Bidang Jasa pada PT. Hotel Sahid Jaya Internasional, Tbk - Afrizal Aziz; Rosanni Manullang; Rifat Anggi Agustian (Journal of Academia Perspectives, 2022)
The tourism sector is growing rapidly at this time, one of which is in the field of hospitality, now there are many hotels in tourism areas which are quite a lot of types of hotels from star-class hotels to jasmine class, one of which is PT. Hotel Sahid Jaya International, Tbk which has received the status of a five-star hotel. The purpose of this study was to identify and analyze cash flow statements to assess financial performance at PT. Hotel Sahid Jaya International, Tbk during the period 2016 to 2020. The research method is a descriptive study with a qualitative approach. The method of analysis is cash flow statement analysis where this analysis provides information about the sources and uses of cash. The results of this study are based on cash flow ratio analysis conducted at PT. Hotel Sahid Jaya International, Tbk is still not good enough, where in the cash flow statement from 2016 to 2020 it continues to decline every year since 2017. Where only the capital expenditure ratio (PM) and the cash to interest coverage ratio (CKB) are significant. the ratio value reaches the standard